Effect of Group-based Fallproof Program on Balance and Psychological Health of the Elderly With Different Ages - Pegah Rajabpour; Masoumeh Shojaei; Abdollah Ghasemi; Keyvan Molanorouzi (Shahid Beheshti University of Medical Sciences, 2023)
Background and Aims Balance control is needed to walk and function independently. Decreased balance accompanied by fear of falling can have a negative effect on the mental and physical health of older adults. In this study, we aim to assess the effect of group-based Fallproof program on balance and psychological aspects of health in the elderly with different ages.Methods In this quasi-experimental study, the study population consists of all healthy community-dwelling older people in Tehran, Iran. Based to the inclusion criteria, 60 people aged 65-85 years were selected using a convenience sampling method from public recreational centers. They were divided into three age groups: 65-71, 72-78, and 79-85 years. All groups received a group-based Fallproof program for eight weeks, three times a week. The Symptoms Checklist-90-Revised was used to measure psychological problems, and the Fullerton Advanced Balance scale was used to identify balance problems in the pre-test and post-test phases. Kolmogorov-Smirnov test was used to evaluate the normality of data distribution, and analysis of covariance was used to measure the mean differences between groups The significance level was set at 0.05.Results The results showed a significant improvement in balance and psychological health of all three groups after the intervention (P<0.001). The oldest group showed more significant improvement in all dependent variables when compared to other two groups. Therefore, older adults not only can benefit from exercise-based interventions, but also can achieve better physical and psychological results in short period by participating in group-based Fallproof program.Conclusion Eight weeks of group-based Fallproof program can be effective in improving balance and psychological health of the elderly and can be used along with other training protocols for improving balance problems of older adults.